The military option in the Iranian nuclear crisis - Rieger, René (2012)
Abstract: "The Iranian nuclear crisis has reached a new peak. An Israeli air strike on Iran’s nuclear facilities is more likely than ever. However, such a pre-emptive attack would not only be in breach of international law it would also fail to serve Israel’s interests. On the contrary, a military attack would put Israel’s security in jeopardy both in the short and long run and could provoke a regional war as well as an oil crisis of unprecedented magnitude. Therefore, the EU and its member states should persuade Israel to refrain from a pre-emptive strike against Iran. In contrast, Europe should advocate firmly a peaceful conflict resolution grounded on incentive-based negotiations with Tehran." [authors abstract]